Theoretical and Philosophical Fundamentals of the Sharia Economic System in the Context of the Modern Economic System - Chandra; Hasan Bisri; Ija Suntana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Economics based on sharia has concepts and teachings that can provide welfare evenly to mankind. Therefore, the philosophy of Islamic economics is the main key in human economic development. The purpose of this paper is to discuss the existence of sharia economic philosophy in the modern era. The golden opportunity for the growth of Islamic Economics developed in Indonesia needs to be supported by knowing the western response to economic conditions in Indonesia, where the 4.0 revolution era is a challenge for Indonesia in the economic welfare of its people. Therefore, in order to find the response and contribution of Sharia economic philosophy to the western system that tends to be modern. This type of research is normative juridical and descriptive legal study. The results of the study found that Sharia economic philosophy has very strong energy to ensure that the modern economy is established and strong. Without a philosophical basis packed by Islamic values, the economic system looks weak. So that the Sharia economy in Indonesia is embracing the Indonesian sharia economy with the aim of re-controlling the indo pacific, by implementing a free market and capitalist system. However, Indonesia remains in principle, namely developing the potential of the Islamic economy because this is a golden opportunity towards an established and progressive Indonesia.